The SAGE encyclopedia of psychology and gender - Nadal, Kevin L. (Thousand Oaks, CA : SAGE Publications, Inc., 2017)
The SAGE encyclopedia of psychology & gender is an innovative exploration of the intersection of gender and psychology--topics that resonate across disciplines and inform our everyday lives. This encyclopedia looks at issues of gender, identity, and psychological processes at the individual as well as the societal level, exploring topics such as how gender intersects with developmental processes both in infancy and childhood as well as throughout later life stages; the evolution of feminism and the men's movement; the ways in which gender can affect psychological outcomes and influence behavior; and more. With articles written by experts across a variety of disciplines, this encyclopedia brings insights on the psychology of gender, through the lens of developmental science, social science, clinical and counseling psychology, sociology, and more. ...
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: Gender identity; Developmental psychobiology